2021
DOI: 10.1371/journal.pone.0257924
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of cadmium-induced genotoxicity and oxidative stress in mung bean seedlings by priming effect of phytohormones and proline

Abstract: In this research, eight local mung bean (Vigna radiata) varieties were analyzed for their performance against two levels of CdCl2 solution (0.3 and 0.5 mM) alone and priming with gibberellic acid (GA3) (100 μM), salicylic acid (SA) (50 μM) and proline (5 mM) solution prior to Cd exposure. Mung bean seedlings were analyzed for disturbance in cytological, morphological, biochemical and enzymatic parameters under cadmium stress. For cytological studies, 48 h grown mung bean seedlings root tips were used to prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
(64 reference statements)
2
10
0
Order By: Relevance
“…Similar results (about 250-400 U g −1 fw) were found in mung bean leaves with an exception of a negligible decline due to Cd toxicity (Leng et al 2021). However, as compared to control, an enhanced activity of APX enzyme due to Cd toxicity was observed in mung bean seedlings which also supports our results (Hassan et al 2021). About 19% increased (41.0-67.2 U g −1 fw) CAT activity due to Cd stress was observed in this study which was about 64% higher in mung bean seedlings (Leng et al 2021) as compared to control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results (about 250-400 U g −1 fw) were found in mung bean leaves with an exception of a negligible decline due to Cd toxicity (Leng et al 2021). However, as compared to control, an enhanced activity of APX enzyme due to Cd toxicity was observed in mung bean seedlings which also supports our results (Hassan et al 2021). About 19% increased (41.0-67.2 U g −1 fw) CAT activity due to Cd stress was observed in this study which was about 64% higher in mung bean seedlings (Leng et al 2021) as compared to control.…”
Section: Discussionsupporting
confidence: 91%
“…As compared to the uncontaminated control about 138-139% increased SOD activity was observed in mung beans due to Cd contamination (Ramzani et al 2017). However, under Cd treatments, Hassan et al (2021) found an enhanced SOD activity while a slight decreased activity was observed by Leng et al (2021). In this study, activities of all the antioxidant enzymes were increased with ZnO NPs application under Cd stress.…”
Section: Discussionmentioning
confidence: 43%
“… 72 In addationaly, all antioxidant enzymes and MDA content were also found to have a significant positive correlation. 73 In our studied showed an increase in proline and MDA levels with an increase in the concentration of metallic ions. The fact that this increase was high in the stem portion of the plant was indicative of a correlation between free radical formation and proline accumulation ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 56%
“…In Cd stressed Nicotiana tabacum, exogenous Se treatment increased the levels of indole acetic acid (IAA) [42]. However, seed priming with GA and SA showed stimulatory effects on growth and metabolism of mung bean under Cd stress conditions [43]. Furthermore, role of JA and GA in inducing tolerance to Cd stress is also explored in Cicer arietinum [44].…”
Section: Introductionmentioning
confidence: 99%